DEVELOPMENT OF CURVED SIDE SPACE MODULE TO IMPROVE ABILITY IN UNDERSTANDING MATHEMATICS CONCEPTS - Merry Kris Mawati (Afore : Jurnal Pendidikan Matematika, 2023)
Mathematics is a very important science to be learned and mastered by students at school. Mathematics lessons are still considered difficult by students in understanding the material and which has an impact on student learning outcomes. The aims of this research are to produce a valid, practical, and effective curvature side structure module, and to improve students' ability to understand mathematical concepts in the Curved Side Spatial Building material. This type of research is Research and Development (R&D), the development model used is the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. Data collection techniques used in this study were questionnaires, tests, and interview guidelines. While the data analysis techniques are qualitative data analysis and quantitative data analysis. Based on research and discussion that the validation test results from material expert validators are 92.66% with very feasible criteria, validation test results from media expert validators are 71.98% with feasible criteria, and validation test results from linguist validators are 98% with very decent criteria. The results of the practicality test of the student respondents for the individual test were 87.81% the criteria were very interesting and very practical, the results of the student respondents for the small group test were 86.16% the criteria were very interesting and practical. The results of the effectiveness test based on the calculation of N-Gain obtained an average value of 0.74. The developed module can be used to improve the ability to understand mathematical concepts in the material for Constructing Curved Side Space.